Friends. Season 1 [videorecording (DVD)] - Astrof, Jeffrey; Sikowitz, Mike; Junge, Alexa; Greenstein, Jeff; Strauss, Jeff; Chase, Adam (Television writer and producer); Ungerleider, Ira; Lawrence, Bill, 1969-; Abrams, Doty; Brown, Chris (Television writer); Aniston, Jennifer; Cox, Courteney, 1964-; et al. (Warner Bros. Entertainment Inc., 2019)
"Revisit the first year, in which Rachel (Jennifer Aniston), Monica (Courteney Cox), Phoebe (Lisa Kudrow), Joey (Matt LeBlac), Chandler (Matthew Perry), and Ross (David Schwimmer) charmed audiences worldwide." -- Cover.